Evaluation of Intoxication Case Application to the Child Emergency Department Between 2016-2021 - Kırcı, Güven Seçkin; Öztürk, Deniz Utku; Bölükbaşı, Hacı Seyit; Çakır, Hilal; Özer, Erdal (The Bulletin of Legal Medicine, 2023)
Objective: Cases of intoxication are among preventable public health problems. In this study, it is aimed to evaluate the pediatric patients between the ages of 0-18 who applied to the hospital due to intoxication and to discuss them in the light of national and international literature. Methods: The files of 293 pediatric patient due to intoxication in our pediatric emergency medicine clinic between 2016-2021 were reviewed retrospectively. Results: Of 293 pediatric patients aged 0-18 years, who applied to the pediatric emergency service due to intoxication, 153 (52.22%) were female and 140 (47.78%) were male, attempting suicide, conscious/pleasure use, and drawing attention. When the intoxication cases that occurred were examined, it was determined that the majority of them occurred between the ages of 12-18, and all of the intoxication cases with intention of suicide attempt (n=60) o between the ages of 12-18. Conclusion: Intoxication cases both in our country and in the world are known to be among the preventable causes of death. In terms of preventing these cases, it is important to raise awareness as a result of effective scientific training at the community, family and individual level. In terms of health policies, limiting the sale and use of non-prescription drugs, not keeping the corrosive substances, cleaning agents and insecticides used in the house in areas where children can easily reach, and making the outer packaging of them in a way that cannot be opened easily will make a great contribution in terms of preventing possible accidents.